Intraperitoneal Atrial Natriuretic Peptide Attenuates Anxiety-related Behaviour during Alcohol Withdrawal in Mice - von der Goltz, C.; Jahn, H.; Mutschler, J.; Wiedemann, K.; Kiefer, F. (Pharmacopsychiatry, 2014)
Converging evidence from both preclinical and clinical studies suggests atrial natriuretic peptide (ANP) as a potential target for treatment of alcohol withdrawal and dependence. Since ANP tightly interacts with hypothalamic-pituitary-adrenocortical (HPA) axis activity, especially the modulation of stress-related anxiety during alcohol withdrawal might mediate these effects. We have now evaluated the anxiolytic activity of intraperitoneal ANP application during alcohol withdrawal in alcohol-habituated mice (C57/Bl6J). Anxiety related behaviour was attenuated during ethanol withdrawal following application of ANP (60 μg/kg) vs. saline. Our results support that anxiolytic effects of ANP mediate ANP-related gene effects with clinical data on withdrawal symptomatology.
Keywords: ANP; alcoholism; HPA; natriuretic peptides; anxiety